The Prosecutor’s Authority to Conduct a Criminal Investigation Based on The Government Administration Law - Leonardo Adiguna (Fakultas Hukum Universitas Lampung, 2021)
This research uses a normative approach, which is carried out by examining laws and theories. Also, this study uses a case approach, namely the 2017 village fund corruption case in Pekon Sukaratu. The main problem in this research is what is the authority of the prosecutor in conducting investigations into criminal acts of corruption after the passage of Law Number 30 of 2014 concerning Government Administration and whether the investigation carried out by the prosecutor at the Pringsewu District Prosecutor's Office in coordination with the Government Internal Supervisory Apparatus or Aparatur Pengawas Internal Pemerintah (APIP) against the allegations a criminal act of corruption in the management of village funds in 2017 in Pekon Sukaratu whose losses to the state have been returned have met the principle of legal certainty. The research results show that the prosecutor has the authority to carry out the law enforcement process, namely the investigation of suspected corruption crimes as stipulated in Article 30 paragraph (1) letter d of the law on the Prosecutor's Office of the Republic of Indonesia. Based on the results of the research that has been done, it is better if changes in laws and regulations related to the elements of corruption in Law No. 31 of 1999 concerning Eradication of Corruption Crime because there is a product of the Constitutional Court with the decision No. 25/PUU-XIV/2016. Besides, there is a need for socialization for prosecutors regarding their authority in TPK investigations and related to coordination patterns with the authority of APIP in carrying out investigations and calculating state financial losses.